PERSONAL HYGIENE SEBAGAI PREDIKTOR PENYAKIT SKABIES PADA SANTRI DI KELURAHAN KALIBEBER, MOJOTENGAH, WONOSOBO - Rifka Maharani; Dyah Mahendrasari Sukendra (Jurnal Kesehatan Masyarakat, 2023)
Scabies is one of the neglected tropical diseases caused by Sarcoptes scabiei var. hominis. Students is one of the populations at risk of getting scabies because transmission of scabies easily occurs in crowded conditions, such as in islamic boarding school. Kalibeber Urban Village has the largest population of students at islamic boarding schools (48.7%) in Mojotengah Sub-District. The incidence of scabies increased by 1,041,5% in 2021 and was included in the top five diseases at the Puskesmas Mojotengah in 2021. Students do not feel threatened by scabies. According to SMD results, they still underestimate personal hygiene. This study used observational analytic methods using case-control design among students in islamic boarding schools. A total of 69 case samples and 69 control samples were taken through a simple random sampling technique followed by proportional random sampling. Data were analyzed using Chi square, Fisher, and logistic regression. The result of this study showed that when the confounding is controlled by logistic regression, bed sharing (p=0.018; AOR=4,65) related with the incidence of scabies. For the rest, there is no significant relationship between sharing clothes, bathing habit, and hand hygiene habit with the incidence of scabies. Increasing the awareness of students to implement personal hygiene and establishing rules regarding the application of personal hygiene in order to break the chain of transmission of scabies, are recommended.